2019
DOI: 10.1007/s00464-018-06653-2
|View full text |Cite
|
Sign up to set email alerts
|

The oncological and surgical safety of robot-assisted surgery in colorectal cancer: outcomes of a longitudinal prospective cohort study

Abstract: BackgroundColorectal cancer is one of the most common cancers worldwide. Laparoscopic colorectal surgery (LCRS) is a frequently used modality. A new development in minimally invasive surgery is robot-assisted colorectal surgery (RACRS).MethodsProspectively collected data of 378 consecutive patients who underwent RACRS or LCRS for stage I–III colorectal cancer from Dec 2014 to Oct 2017 were analyzed. Primary outcome was oncological outcome (radical margins, number of retrieved lymph nodes, locoregional recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 30 publications
4
40
2
Order By: Relevance
“…Although the results in detail might vary depending on the studies, the recent comparative studies between laparoscopic and robotic TME for rectal cancer showed overall comparable clinical outcomes (Table 1). [40][41][42][43][44][45][46][47][48] In 2008, Baik et al 40 reported a pilot randomized controlled study for comparing robotic and laparoscopic tumor-specific mesorectal excision (TSME) with a small population, the results showed that the mean operative time was not significantly different between the two groups (217.1±51.6 vs. 204.3±51.9, p=0.477). According to Park et al 42 and Polat et al 48 , the operative time also reported no difference.…”
Section: Perioperative Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the results in detail might vary depending on the studies, the recent comparative studies between laparoscopic and robotic TME for rectal cancer showed overall comparable clinical outcomes (Table 1). [40][41][42][43][44][45][46][47][48] In 2008, Baik et al 40 reported a pilot randomized controlled study for comparing robotic and laparoscopic tumor-specific mesorectal excision (TSME) with a small population, the results showed that the mean operative time was not significantly different between the two groups (217.1±51.6 vs. 204.3±51.9, p=0.477). According to Park et al 42 and Polat et al 48 , the operative time also reported no difference.…”
Section: Perioperative Outcomesmentioning
confidence: 99%
“…[40][41][42][43][44][45][46][47][48] In 2008, Baik et al 40 reported a pilot randomized controlled study for comparing robotic and laparoscopic tumor-specific mesorectal excision (TSME) with a small population, the results showed that the mean operative time was not significantly different between the two groups (217.1±51.6 vs. 204.3±51.9, p=0.477). According to Park et al 42 and Polat et al 48 , the operative time also reported no difference. However, except for those studies, the other studies have shown that robotic rectal surgery not only showed longer operative time, [43][44][45][46][47] but also shorter operative time 41 than laparoscopic rectal surgery.…”
Section: Perioperative Outcomesmentioning
confidence: 99%
See 3 more Smart Citations